Mandibular Sagittal Split Osteotomy to High Carotid Pathology: Multidisciplinary Management - Krylov, Vladimir Victorovich; Luk'ianchikov, Victor Aleksandrovich; Gorozhanin, Vadim Aleksandrovich; Fedotov, Roman Nikolaevich; Shatokhin, Taras Andreevich; Reshetov, Dmitrii Nikolaevich (Asian Journal of Neurosurgery, 2025)
Surgical strategies for neck tumors extending to the skull base and high-lying carotid artery pathologies present significant challenges for surgeons, necessitating deviations from traditional neck surgery approaches. These tactics are adopted to expand the surgical approach. Although the mandibular sagittal split osteotomy (MSSO) has been routinely utilized in maxillofacial surgery, its integration into combined surgical approaches for head and neck pathologies has not been widely explored. We present our experience using MSSO in patients with neck pathology. A retrospective analysis was conducted on 12 patients who underwent surgery between 2020 and 2022 for benign neck tumors and vascular pathologies that posed challenges for removal using traditional approaches. All patients underwent surgical treatment utilizing the technique of unilateral MSSO and fragment retraction to enhance the surgical approach for neck pathologies. An evaluation of early postoperative outcomes was performed. Based on the criteria presented, the study group consisted of 12 patients with various histological types of benign tumors (n = 11) and atherosclerotic plaque in the carotid artery (n = 1). Following the osteotomy step, mandibular advancement of an average distance of 17.2 ± 1.6 mm was achieved, allowing for an extended surgical approach on the lateral aspect of the neck measuring 48.7 ± 3.5 mm. This technique facilitated the successful total tumor resection in most of cases. Complications related to the osteotomy were observed in two patients during the early postoperative period, which included malocclusion necessitating plate refixation and hematoma formation in the soft tissues of the neck. The utilization of the unilateral intraoral technique of sagittal split osteotomy with mandibular abduction has demonstrated good outcomes in providing an extended surgical approach for tumors located in the distal neck segment of the internal carotid artery.
Keywords: carotid endarterectomy; mandibular sagittal split osteotomy; mandibular subluxation; neck tumors; split osteotomy; upper neck region